EFFECTS OF CONSUMING BISCUITS MADE FROM MORINGA OLEIFERA LEAF ON BODY WEIGHT AND HEIGHT OF CHILDREN UNDER FIVE IN BANGKALAN, MADURA ISLAND - Anna Surgean Veterini; Enny Susanti; Meity Ardiana; Annis Catur Adi; Heni Rachmawati (Universitas Airlangga, 2023)
One of the efforts to maintain children’s nutritional status is to prevent weight faltering, which was formerly known as failure to thrive. Unresolved weight faltering will cause several problems, such as growth failure, stunting, decreased IQ, morbidity, and mortality in children. Stunting is one of the big problems that occur in Indonesia. One of the continuous strategies to prevent weight faltering is through food supplementation, such as consuming moringa leaf which is high in protein in the form of biscuits. This study aims to determine the effects of consuming biscuits made from Moringa oleifera leaf on children's growth in Bangkalan, Indonesia. This study used experimental research method for two months. The sample was drawn using consecutive sampling technique. The subjects in this study were 31 children under five whose weight and height were not according to age. Before moringa biscuits were distributed, children’s body weight and height were measured. The nutritional status was evaluated every month for two months. The parameters measured were weight gain and height increase. The results were analyzed using univariate and multivariate tests on SPSS. After giving moringa oleifera biscuits for two months at the Village Health Post (Pos Kesehatan Desa/Poskesdes) of Bangkalan, children’s body weight increased by 0.35 kg per month and their height increased by 0.65 cm per month. The distribution of biscuits can be continued to preventing stunting.